Technical report: computing unemployment rates under parallel data / Muhammad Naqiuddin Nasaruddin - Nasaruddin, Muhammad Naqiuddin (2017)
This project is about estimating and suggesting the best unemployment rate. Unemployment in Malaysia has become a major issue as many graduates face difficulties in searching for jobs. Unattended event like this may cause a future problem to our country. This project focus on data of unemployment rate from the year 2009 till 2014. Data is taken from 3 different sources. Department of Statistics Malaysia, The World Bank and Quandl and shows unstable value on rate on unemployment over the year 2009 to 2014. A new data that was improved by computing the 3 data were compared to prediction of each actual data. The project shows that by improving the data, the result obtain will be a value that can be used to represent all data from different source if data were taken from more than one source.